Тайна "Коварной русалки": [повесть] / Антон Иванов, Анна Устинова - Иванов Антон Давидович (Детектив & Приключения, 2015)
Экземпляры: ФО-10 (20160129) / Инвентарный номер: 48989z1 / Цена: / Авт.знак: И 20 / ББК: 84(2Рос=Рус)6